Synthesis of α-Fe2O3 Dispersed Polyvinyl Alcohol Nanocomposite Film - Kumar Lagashetty, Arun; Mallikarjuna, N.N.; Venkataraman, A. (Asian Journal of Chemistry, 2010)
α-Fe2O3 was purified from commercially available red oxide (lS-445). This purified α-Fe2O3 was dispersed in polyvinyl alcohol having m.w. 1,25,000 (obtained commercially by Mis Himedia Chemicals, Mumbai) through solvent casting method. The structure of synthesized composite film was studied by X-ray diffraction pattern (XRD) and morphology was studied by scanning electron micrograph (SEM). The variations in vibrational frequencies were studied by infrared studies.